Investigating Hypovitaminosis D and Childhood Nephrotic Syndrome: An Observational Study to Find Subjects in Need of Attention: Hypovitaminosis D in Nephrotic Syndrome - Nandi, Sayantani (Journal of Pediatric Nephrology, 2025)
Background and Aim: Nephrotic syndrome (NS) is associated with variable ranges of vitamin D deficiency in the pediatric population. This study examines the vitamin D status in children with NS during active disease in a tertiary care center in eastern India. Methods: This observational study was conducted for 18 months in a tertiary care hospital taking 60 cases of NS of 2-12 years of age and 30 age- and sex-matched controls. Serum 25(OH) vitamin D and alkaline phosphatase (ALP) levels were assayed and analyzed. Results: In this study, the mean vitamin D level (12.54±6.85 ng/mL) in cases was significantly lower (P=0.002) compared to the control group (22.1±5.8 ng/mL). Mean vitamin D level was low in all groups of NS cases and the lowest in steroid-resistant NS (SRNS) followed by steroid-dependent NS (SDNS)/frequent relapse NS group. Vitamin D insufficiency (12- 20 ng/mL) was more prevalent in the first episode whereas deficiency (<12 ng/mL) was more common in subjects with relapse. Serum ALP levels were raised in 35% of vitamin D deficient cases but normal in the rest of the deficient, all insufficient, and sufficient cases. Conclusion: Hypovitaminosis D was more common in children with NS as compared to the general pediatric population irrespective of sex. Vitamin D status varied according to the course of the disease of NS. A strong negative correlation of vitamin D status and serum ALP was observed in children with NS but serum ALP level for screening of vitamin D status could not be used.